2016
DOI: 10.5505/tjtes.2016.11823
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia modified albumin and other inflammatory markers in the diagnosis of appendicitis in children

Abstract: BACKGROUND:The aim of the present study was to determine relationship of ischemia-modified albumin (IMA) level, C-reactive protein (CRP) level, erythrocyte sedimentation rate (ESR), white blood cell (WBC) count, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV) to appendicitis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 12 publications
2
20
1
3
Order By: Relevance
“…The sensitivity of the WCC in acute appendicitis ranges from 65-89.4% with a specificity of 55-80% in studies done in HICs; 3,[22][23][24][25] in comparison, our results show a lower sensitivity and specificity of 69.6% and 43.1%, respectively. This may perhaps be attributed to the higher incidence of other infections in our populations such as tuberculosis and worm infestation.…”
Section: Discussionmentioning
confidence: 52%
“…The sensitivity of the WCC in acute appendicitis ranges from 65-89.4% with a specificity of 55-80% in studies done in HICs; 3,[22][23][24][25] in comparison, our results show a lower sensitivity and specificity of 69.6% and 43.1%, respectively. This may perhaps be attributed to the higher incidence of other infections in our populations such as tuberculosis and worm infestation.…”
Section: Discussionmentioning
confidence: 52%
“…In their study, Dumlu et al (29) also observed increased IMA levels in the AG than in the CG. In a study conducted in children, Nazik et al (30) observed that IMA levels were elevated in AA. Kılıç et al (31) suggested that IMA levels in adult AA patients are significantly elevated and can be used as an indicator of appendicitis severit.…”
Section: The Demographic Results Of Groupsmentioning
confidence: 98%
“…In a recent study, NLR, and PLR were evaluated in patients treated for familial Mediterranean fever 19 ; PLR was deemed increased in patients with the condition compared with the control group. In another study by Nazik 20 , use of NLR, PLR, IMA, and ESR values may be helpful in the diagnosis of appendicitis. In our study, PLR was increased with in ammation and was higher in the perforated appendectomy group (237.51 ± 149.98).…”
Section: Discussionmentioning
confidence: 99%